The climate, the fuel and the land use: Long‐term regional variability of biomass burning in boreal forests. (20th July 2018) - Molinari, Chiara; Lehsten, Veiko; Blarquez, Olivier; Carcaillet, Christopher; Davis, Basil A. S.; Kaplan, Jed O.; Clear, Jennifer; Bradshaw, Richard H. W.
Abstract: The influence of different drivers on changes in North American and European boreal forests biomass burning (BB) during the Holocene was investigated based on the following hypotheses: land use was important only in the southernmost regions, while elsewhere climate was the main driver modulated by changes in fuel type. BB was reconstructed by means of 88 sedimentary charcoal records divided into six different site clusters. A statistical approach was used to explore the relative contribution of (a) pollen‐based mean July/summer temperature and mean annual precipitation reconstructions, (b) an independent model‐based scenario of past land use (LU), and (c) pollen‐based reconstructions of plant functional types (PFTs) on BB. Our hypotheses were tested with: (a) a west‐east northern boreal sector with changing climatic conditions and a homogeneous vegetation, and (b) a north‐south European boreal sector characterized by gradual variation in both climate and vegetation composition. The processes driving BB in boreal forests varied from one region to another during the Holocene. However, general trends in boreal biomass burning were primarily controlled by changes in climate (mean annual precipitation in Alaska, northern Quebec, and northern Fennoscandia, and mean July/summer temperature in central Canada and central Fennoscandia) and, secondarily, by fuel composition (BB positively correlated with the presence of boreal needleleaf evergreen trees in Alaska and in central and southern Fennoscandia). Land use played only a marginal role. A modification towards less flammable tree species (by promoting deciduous stands over fire‐prone conifers) could contribute to reduce circumboreal wildfire risk in future warmer periods. Abstract : The influence of different drivers on changes in North American and European boreal forests biomass burning (BB) during the Holocene was investigated based on the following hypotheses: (H1) climate drove Holocene trends in BB in regions with the same fuel type; (H2) climate‐controlled patterns of Holocene BB were mitigated at a regional scale by trees' flammability; (H3) land use had a limited explanatory power during most of the Holocene, except for the southernmost European boreal regions concerned by farming practices.